Analysis of physical pore space characteristics of two pyrolytic biochars and potential as microhabitat - Schnee, Laura S.; Knath, Stefan; Hapca, Simona; Otten, Wilfred; Eickhorst, Thilo (Springer, 2016)
Background and Aims Biochar amendment to soil is a promising practice of enhancing productivity of agricultural systems. The positive effects on crop are often attributed to a promotion of beneficial soil microorganisms while suppressing pathogens e.g. This study aims to determine the influence of biochar feedstock on (i) spontaneous and fungi inoculated microbial colonisation of biochar particles and (ii) physical pore space characteristics of native and fungi colonised biochar particles which impact microbial habitat quality. Methods Pyrolytic biochars from mixed woods and Miscanthus were investigated towards spontaneous colonisation by classical microbiological isolation, phylogenetic identification of bacterial and fungal strains, and microbial respiration analysis. Physical pore space characteristics of biochar particles were determined by X-ray μ-CT. Subsequent 3D image analysis included porosity, surface area, connectivities, and pore size distribution. Results Microorganisms isolated from Wood biochar were more abundant and proliferated faster than those from the Miscanthus biochar. All isolated bacteria belonged to gram-positive bacteria and were feedstock specific. Respiration analysis revealed higher microbial activity for Wood biochar after water and substrate amendment while basal respiration was on the same low level for both biochars. Differences in porosity and physical surface area were detected only in interaction with biochar-specific colonisation. Miscanthus biochar was shown to have higher connectivity values in surface, volume and transmission than Wood biochars as well as larger pores as observed by pore size distribution. Differences in physical properties between colonised and non-colonised particles were larger in Miscanthus biochar than in Wood biochar. Conclusions Vigorous colonisation was found on Wood biochar compared to Miscanthus biochar. This is contrasted by our findings from physical pore space analysis which suggests better habitat quality in Miscanthus biochar than in Wood biochar. We conclude that (i) the selected feedstocks display large differences in microbial habitat quality as well as physical pore space characteristics and (ii) physical description of biochars alone does not suffice for the reliable prediction of microbial habitat quality and recommend that physical and surface chemical data should be linked for this purpose.
Keywords: Biochar; Microbial colonisation; Pore geometry; Habitat quality